IMPLEMENTATION OF MEDICAL CHECKS (MCU) IN THE WORKFORCE IN HOTEL COMPANIES - Helviana Hasibuan; Irsyam Risdawati; Ismaidar Ismaidar (Universitas Labuhanbatu, 2024)
Considering the risk of infection and spread of disease in the workplace, it is necessary to provide health checks or what is called a medical check-up (MCU) for workers. This research aims firstly to find out how medical check-ups are implemented for workers and, secondly to find out the supporting and inhibiting factors for implementing medical check-ups at the Santika Premiere Dyandra Hotel Medan. This research uses qualitative research, which is descriptive using a theoretical basis to present information according to facts in the field, interview data collection techniques, and documentation. The results of the research show firstly, Hotel Santika Premiere Dyandra Medan has implemented medical check-ups for its workforce but it is still not optimal by Minister of Manpower Regulation 02 of 1980 concerning the Implementation of Occupational Health Checks. Supporting factors for carrying out medical check-ups are government regulations and hotel SOP rules which require workers to carry out medical check-ups, while the inhibiting factor for carrying out medical check-ups at hotels is the high cost of medical check-ups at hospitals/clinics.Key words: Hotels; Occupational health and safety (K3); Medical check-up